PERUBAHAN KOMPOSISI PATI PADA TEPUNG PISANG KAPAS (Musa comiculata) TERMODIFIKASI SECARA FERMENTASI SPONTAN DAN LAMA PEMANASAN BERTEKANAN-PENDINGINAN - Miftakhur Rohmah (PROSIDING SEMINAR KIMIA, 2014)
Kapas banana is a source of carbohydrate that can used as flour. Physical and chemical properties of the natural flour have abstacle that caused limited apllication for food product. Banana flour can be modified by spontaneous fermentation and autoclaving -cooling to increase the function of the flour. Thisstudy aims to determine strach, amylose and amy lopectin content. This experiment used completely randomized design with two factorial and three replication. The first factor was spontaneous fermentation in 0, 12, 24, and 45 hour, whereas the other was autoclaving - cooling in 0 , 15 , 30 and 45 minute. Result of the experiment showed that modification of spontaneous fermentation and autoclaving the affect the characteristic of kapas banana flour . The content of starch, amylose, and amylopectin in the kapas banana flour are 58.56-71.70 %, 14.58-20.46 %, and 39.66-54.03 % respectively.